Model Development of Class IIA Inmates in Pekalongan City - Darsono, Budi; Suyahmo, Suyahmo; Rodiyah, Rodiyah (Universitas Negeri Semarang, 2017)
Up to now, the class IIA prison in Pekalongan has implemented coaching program for the assisted citizens in the form of personal development activities and self-development activities. Not all personality building activities and self-help activities are followed by all the targeted people, except health counseling activities and sport ones. Even for guidance and counseling for Buddhism and Hinduism is not there. This makes most of the assisted people were not monitored his development, both in terms of mental formation, character and creativity. The guidance is not followed by all inmates and they only follow the coaching according to their interests and talents respectively, so less be a provision of life later in the day if it is out of prison. For that reason, we need integrated coaching. The purpose of this research is to be able to apply the ideal and proper guidance model for the assisted people in Penitentiary Class II A Pekalongan. The results of the research can be submitted that the number of prisoners of June 20th, 2017 of 446 assisted citizens who are active in independence activity and special skills are only small part, they are: Bismawat Block consists of 45 persons, Block III consists of 38 persons, Block IV consists of 16 people and Block V consists of 23 people. So there are only 27.35% (122 persons) from 446 person who are active joining the program. The coaching model is still based on the interests and talents of the assisted citizens in accordance with their abilities, so it has not seen an integrated coaching model from one activity to another.